2021
DOI: 10.1093/insilicoplants/diab008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of soybean (Glycine max L.) adaptation to northern European regions under different agro-climatic scenarios

Abstract: Soybean is a candidate crop to increase the independency of Europe in leguminous protein crops. However, its adaptation to northern European regions is not yet well defined due to lack of long-term references. Herein, we simulated soybean yield potential in northern France and identified the main yield limiting factors under rainfed vs irrigated conditions. Two cultivars representing maturity groups 000 and 00 were planted within three different trials. Leaf area index, shoot and pod biomass, main phenological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…The thermal time from sowing to pod maturity (R8) was also not correlated with R2R5 or R5R8. A long duration of reproductive development has been proposed as a strategy to improve soybean yield without affecting the total length of the growing cycle ( Metz et al, 1985 ; Cooper, 2003 ), and a simulation study predicted a positive relationship between yield and the thermal time to flowering and pod maturity in Northern Europe ( Boulch et al, 2021 ). Our results indicate that the EUCLEG collection contains accessions with the required combination of a long duration of reproductive development and high values of yield traits, with possibly no direct impact on the total length of the growing period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The thermal time from sowing to pod maturity (R8) was also not correlated with R2R5 or R5R8. A long duration of reproductive development has been proposed as a strategy to improve soybean yield without affecting the total length of the growing cycle ( Metz et al, 1985 ; Cooper, 2003 ), and a simulation study predicted a positive relationship between yield and the thermal time to flowering and pod maturity in Northern Europe ( Boulch et al, 2021 ). Our results indicate that the EUCLEG collection contains accessions with the required combination of a long duration of reproductive development and high values of yield traits, with possibly no direct impact on the total length of the growing period.…”
Section: Discussionmentioning
confidence: 99%
“…In soybean, a longer period of grain filling has been shown to be advantageous for yield potential at high latitudes ( Cooper, 2003 ). A simulation study estimated an optimum grain filling duration of 60 days for soybean in Northern France ( Boulch et al, 2021 ). In our experiments, drought lengthened the duration of seed development (R5R8, corresponding to the seed filling duration), which was due to an earlier shift to R5 (start of seed formation) which led a shortening of R2R5 (corresponding to the period during which new flowers and pods are formed).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soybean ( Glycine max L.) is worldwide the most cropped legume, as it represents a vital source of vegetable protein for both humans and livestock ( Wang et al., 2022 ). Soybean is sensitive to low soil moisture, however, it is adapted to a large range of temperatures, and its cultivation is extended toward Northern Europe ( Boulch et al., 2021 ; Karges et al., 2022 ). Despite that, little is known about the soybean response and resilience capacity to various drought events at different growth stages, under European conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This requires breeding soybean varieties welladapted to the European environmental and cultivation conditions. While North West Europe is often considered a humid region, simulations have demonstrated that water can be the main limiting factor in soybean production, because in general water availability is not well distributed along the crop cycle [52]. In addition, drought spells associated with low rainfall and high temperature are becoming more frequent in Europe during the summer [53][54][55], and forecasts on climatic change predict that the frequency of these events will increase in the future [56].…”
Section: Introductionmentioning
confidence: 99%